Silicon composition material for use as a battery anode - Patents.com
By using copper or titanium films as conductive substrates on the carbon base electrode of lithium-ion batteries and covering the nanostructured amorphous silicon film, the problems of low specific capacity of carbon base electrodes and pulverization and peeling of silicon base electrodes in existing lithium-ion batteries are solved, and higher storage capacity and longer battery life are achieved.
Patent Information
- Application Number
- JP2022506754
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-14
- Filing Date
- 2020-08-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-08-13
AI Technical Summary
The carbon base electrode of existing lithium-ion batteries has a low specific capacity, and the silicon base electrode is easily crushed and peeled off during the lithiation process, resulting in a shortening of battery life and safety hazards.
A film of copper or titanium is used as a conductive substrate to cover a composite layer including silicon, and a nanostructured amorphous silicon film is formed by low-voltage plasma chemical gas deposition (PECVD) technology. The film consists of a number of silicon columns and nanoparticles perpendicular to the surface of the base, which enhances the adhesion between the silicon and the base and reduces crushing and peeling.
It improves the storage capacity per unit mass and volume of lithium-ion batteries, extends the stability and service life of the battery, and reduces the production cost of the battery, making it more suitable for industrial production.
Smart Images

Figure 0007654633000002 
Figure 0007654633000003 
Figure 0007654633000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon (Si) composite material containing copper (Cu) or titanium (Ti) foil that is useful for battery anodes. It further relates to a method for producing the silicon composite material containing copper or titanium foil. Such anode materials are very useful in batteries because they have a much higher specific capacity than currently used anode materials. [Background technology]
[0002] Energy storage devices, including batteries and capacitors, are used in a variety of applications. Due to their relatively high energy density, relatively high specific energy, light weight, and potentially long service life, advanced rechargeable batteries are desirable for a wide range of consumer electronics, electric vehicles, power grid storage, and other important (future) applications. However, despite the increasing commercial popularity of lithium (Li)-ion batteries, further development of these batteries is needed, especially for potential applications in low or zero emission hybrid or fully electric vehicles, drones, consumer electronics, energy efficient cargo ships and locomotives, aerospace applications, and power grids.
[0003] Currently, graphite is generally used industrially as a material for the anode of rechargeable lithium-ion batteries due to its reversible intercalation of lithium ions without significant volumetric (about 10%) and morphological changes. The relatively low specific capacity of graphite (370 mA h / g) that limits the specific capacity of lithium-ion batteries is a major drawback. Silicon's high theoretical lithium-ion storage specific capacity of about 3,579 mAh / g compared to other materials has made it a promising alternative to carbon-based anodes for various types of rechargeable batteries. In practice, only low capacities have been achieved. To date, silicon has only been commercialized as an enhancing additive for carbon-based anodes. One barrier to the full implementation of silicon-based electrodes is the fact that Li-Si electrodes undergo a high degree of pulverization and spalling upon lithiation. Crushing of the active silicon material can cause a shorter service life of the battery and potentially create safety issues due to short circuits in the battery.
[0004] In WO2015175509, a silicon anode is proposed in which silicon is deposited on a nanowire template containing silicon or carbon. The disadvantage of this method is that it requires various complicated fabrication steps, making the fabrication process quite expensive, making the fabrication of silicon anode materials unattractive. Also, scalability to the industrial production level required for commercialization may be difficult.
[0005] In WO2016163878, silicon anodes are proposed that include a nanostructured thin film layer that includes a plurality of adjacent columns extending vertically from the anode surface, where the columns include silicon having an amorphous structure in which nanocrystalline regions are present. A disadvantage of these anodes is that they are susceptible to desorption of silicon from the anode surface.
[0006] Thus, there is a need for alternative materials and techniques for the preparation of silicon containing anodes. Additionally, there is a need for delamination resistant anodes that are suitable for many battery applications. Furthermore, there is a need to manufacture these anodes and batteries by economically attractive processes. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2015175509 [Patent Document 2] International Publication No. 2016163878 Summary of the Invention [Problem to be solved by the invention]
[0008] It is an object of the present invention to provide novel silicon-containing anodes. Another object of the present invention is to provide silicon anodes with higher resistance to spalling and / or pulverization of silicon for various battery applications. A further object of the present invention is to use these anodes in rechargeable batteries. A still further object of the present invention is to provide a method for manufacturing these anodes. [Means for solving the problem]
[0009] The present invention thus relates to a silicon composite material for use as a rechargeable battery anode, comprising: (i) an electrically conductive substrate comprising a copper or titanium foil; (ii) an adhesive layer attached to the foil comprising at least one or more metals and / or metal compounds; and (iii) an electrode layer comprising silicon attached to the adhesive layer.
[0010] The present invention further relates to a rechargeable battery comprising an electrolyte, a cathode layer, a separator layer and a silicon composite material, the electrolyte layer comprising a lithium salt compound disposed between the cathode layer and the silicon composite material.
[0011] The present invention also relates to a method of preparing a silicon composite material for use as a rechargeable battery anode, the silicon composite material comprising: (i) an electrically conductive substrate comprising a copper or titanium foil; (ii) an adhesion layer attached to the foil comprising at least one or more metals and / or metal compounds; and (iii) an electrode layer comprising silicon attached to the adhesion layer by low pressure PECVD.
[0012] One advantage of the present invention is that the silicon formation process is a self-organizing and spontaneous process that forms a continuous amorphous layer nanostructured with multiple columns, nanoparticle aggregates, and interfaces between them in the adhesion layer, resulting in a rechargeable battery with increased storage capacity per unit mass, reduced capacity fade, and improved stability over time. The interfaces in the nanostructured amorphous anode layer are locally perpendicular to the surface of the metal foil that serves as the substrate. The adhesion layer prevents the silicon from peeling off and / or reduces pulverization.
[0013] The method of the present invention can be designed as a single-step fabrication process, for example, without requiring post-treatment steps for the substrate and / or silicon anode layer, thereby facilitating industrial production levels for commercialization.
[0014] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. The terms used in the description of the present invention herein are for the purpose of describing particular embodiments only and are not intended to be limiting of the present invention.
[0015] As used herein, the term "anode" refers to a current collector coated on one or both sides with an electrode material.
[0016] The term "copper or titanium foil" as used herein includes sheet-like material having a thickness in the range of 5-50 micrometers produced by either cold rolling or electroplating, and may include alloys of copper or titanium with elements such as magnesium (Mg), zinc (Zn), tin (Sn), phosphorus (P) and / or silver (Ag). It may be smooth or textured, preferably has a tensile strength in the range of 150-600 MPa, and may include a passivation layer deposited on the copper foil to protect it from oxidation in air.
[0017] The term "CVD," as used herein, includes any process in which a thin coating of a solid material is formed on a solid substrate at high temperature by chemical reaction between a vapor or gas.
[0018] The term "PECVD process" as used herein includes all processes of plasma-enhanced chemical vapor deposition (PECVD) that use plasma generated with the aid of electromagnetic waves in the microwave (MW), very high frequency (VHF), radio frequency (RF) frequency ranges, or using DC electric fields, or extended thermal plasma (ETP), to promote the chemical reaction that forms silicon.
[0019] The term "low pressure PECVD" as used herein refers to PECVD processes where the operating pressure is in the range of 0.01-10 mbar.
[0020] The term MW-PECVD is used herein to refer to a PECVD process in which microwaves are used to generate the plasma.
[0021] The term "silicon layer" as used herein refers to a layer having a thickness of 5-50 micrometers of silicon, hydrogenated silicon or doped silicon, which may be either amorphous, crystalline or a mixture of amorphous and crystalline.
[0022] The term "hydrogenated silicon" or "a:SiH" refers to amorphous silicon with a hydrogen concentration of up to 20%.
[0023] The term "amorphous silicon" should be interpreted to include proto-crystalline silicon, which is the definition of amorphous silicon that includes a certain percentage of nanocrystalline silicon. This percentage may be up to about 30% of the nanostructured silicon thin film layer. For ease of reference, the term amorphous silicon will be used hereinafter to indicate that the nanostructured silicon thin film layer includes amorphous silicon, where the nanocrystalline regions of the nanostructured silicon thin film layer may include a percentage of nanocrystalline silicon up to about 30%.
[0024] It is further noted that in addition to or as an alternative to "silicon", the column may comprise a silicon-based material, i.e. a silicon-based alloy or a silicon-based mixture. Thus, the term "silicon" should also be interpreted to include a silicon-based material, i.e. a silicon-based alloy or a silicon-based mixture. The column may comprise either amorphous silicon or an amorphous silicon alloy, or a combination of amorphous silicon and amorphous silicon alloy.
[0025] The term "doping of silicon" refers to silicon that contains trace amounts of one of the elements N, P, B, Al, C, which increases the conductivity or improves the crystal structure of the silicon.
[0026] The silicon composite device according to the invention is designed for use in a rechargeable battery as an anode, and comprises (i) an electrically conductive substrate comprising a copper or titanium foil, (ii) an adhesive layer attached to the foil comprising at least one or more metals and / or metal compounds, and (iii) an electrode layer comprising silicon attached to the adhesive layer.
[0027] Prior art anodes containing silicon have been tested and have shown problems with pulverization or desorption of the silicon and loss of capacity after multiple charging cycles.
[0028] Applicant has surprisingly found that when silicon is deposited on copper or titanium foil, the adhesion of the silicon to the foil increases when the foil is coated with a metal or metal compound to form an adhesive layer. Surprisingly, in this way, greater resistance to delamination and / or pulverization of the silicon is achieved for various battery applications.
[0029] The adhesive layer comprises at least one or more metals and / or metal compounds different from the metal of the foil itself, thus a copper foil comprises at least one or more metals and / or metal compounds that are not copper and / or copper compounds, and a titanium foil comprises at least one or more metals and / or metal compounds that are not titanium and / or titanium compounds themselves.
[0030] Advantageously, the adhesive layer attached to the copper or titanium foil comprises zinc or tin or a compound thereof. More advantageously, the adhesive layer attached to the foil comprises an oxide of zinc and / or tin. This layer of zinc or tin or an oxide thereof increases the adhesion between the silicon and the copper or titanium foil, since a different complex of silicon is formed at the interface between the foil and the silicon. Even more advantageously, the oxide of zinc is doped with aluminum (Al) and the oxide of tin is doped with fluorine (F) or indium (In) to further increase the electrical conductivity of the layer.
[0031] It is most preferred to use a copper foil coated with zinc oxide, ZnO. The application of ZnO or SnO2 increases the adhesion between the silicon layer and the metal foil.
[0032] To prepare such an adhesive layer attached to the foil, preferably physical vapor deposition (PVD), chemical vapor deposition (CVD) or electrodeposition is utilized. The layer is preferably less than 50 nm thick.
[0033] A silicon layer is preferably present on both sides of the copper or titanium foil, and an adhesion layer composed of one or more metals and / or metal compounds is also preferably present on both sides of the copper foil, thereby increasing the anode capacity per volume unit of use.
[0034] The adhesion layer of one or more metals and / or metal compounds on the copper or titanium foil is preferably up to 5 nm thick, more preferably in the range of 1 to 2 nm.
[0035] Advantageously, the adhesive layer covers at least 50% of the surface of the copper or titanium foil, more preferably at least 80% of the surface, even more preferably at least 90% of the surface, most preferably at least 95% of the surface. Preferably, the layer is a smooth layer having an equal thickness.
[0036] Advantageously, the adhesion layer can be produced by electrochemically coating a copper foil with one or more metals and / or metal compounds and oxidizing the one or more metals and / or metal compounds to their oxides. Alternatively, the metals and / or metal compounds can be deposited using physical vapor deposition techniques such as sputtering of metal and / or metal compound targets, or electron beam or laser ablation of such targets, or it can be deposited using CVD, PECVD, or atomic layer deposition, or plasma-enhanced atomic layer deposition techniques using metal-organic metal precursors and oxidizing agents such as water or oxygen, or plasma of water or oxygen. These depositions can be carried out in separate deposition processes or can be integrated into the silicon deposition process used to produce the anode. Preferably, the adhesion layer is deposited using electrodeposition, physical vapor deposition, plasma-enhanced chemical vapor deposition, or atomic layer deposition.
[0037] The silicon layer is attached to the adhesive layer as a thin film layer preferably comprising a plurality of adjacent columns and agglomerated particles having diameters ranging from at least 5 nm to 50 nm, more preferably from 10 to 20 nm, the columns extending vertically from the copper foil surface, adjacent columns being separated by vertically extending column boundaries.
[0038] The silicon layer preferably has an amorphous structure with nanocrystalline regions present, more preferably the columns contain up to 30% nanocrystalline silicon.
[0039] According to an embodiment, the nanostructured silicon thin film layer advantageously comprises n-type or p-type dopants to obtain a nanostructured silicon thin film layer of n-type conductivity or p-type conductivity, respectively.
[0040] Advantageously, the silicon column further comprises a silicon alloy or composite, preferably selected from the group comprising Si-C and / or Si-N.
[0041] The silicon alloy may be either in addition to or as an alternative to amorphous silicon. Thus, according to an aspect of the invention, the material of the column comprises at least one material selected from amorphous silicon and an amorphous silicon alloy. According to a further aspect, the material of the column comprises amorphous silicon and a nanocrystalline silicon alloy. In some embodiments, the silicon alloy may be present in the electrode layer as a nanocrystalline phase.
[0042] The anode layer may also comprise a mixture of amorphous material and nanocrystalline phases, for example a mixture of amorphous silicon and nanocrystalline silicon, or a mixture of amorphous silicon with a nanocrystalline silicon alloy, or a mixture of silicon in a predominantly amorphous state and a silicon-based alloy, with a certain percentage (up to about 30%) of the mixture in the nanocrystalline state.
[0043] According to the present invention, the amorphous silicon columns preferably extend vertically from the anode surface (i.e., the interface between the anode layer and the electrolyte layer), where multiple silicon columns are disposed adjacent to one another while being separated by interfaces extending perpendicular to the anode surface.
[0044] Advantageously, the electrode layer comprising silicon has a porosity of between 10% and 50% with a pore size in the range 10-40 nm, preferably measured using the Barrett-Joyner-Halena method.
[0045] Silicon composite materials for use as rechargeable battery anodes preferably have a thickness of from 1 μm to 30 μm, preferably from about 10 μm to 20 μm, or from 2.5 to 4.0 mg / cm 2 The electrode layer has a mass filling of up to 1000 .mu.m.
[0046] The present invention is further directed to a rechargeable battery comprising an electrolyte, a cathode layer, a separator layer and a silicon composite material as described above, the electrolyte layer comprising a lithium salt compound disposed between the cathode layer and the silicon composite material. The cathode of the rechargeable battery is preferably nickel manganese cobalt oxide, lithium cobalt oxide, lithium cobalt aluminum oxide, lithium manganese oxide, or lithium iron phosphate. Nickel manganese cobalt oxide is most preferred as it provides the highest specific capacity, but other suitable materials may be used as well.
[0047] The rechargeable battery of the present invention exhibits higher storage capacity per unit mass and volume than prior art lithium-ion batteries, since the use of silicon allows the storage of a larger amount of lithium per unit volume and mass. As a result, the specific capacity of the anode-separator-cathode stack filled with electrolyte can reach up to 480Wh / kg (140Ah / kg at a voltage of 3.5V). Furthermore, the open nanostructure of the electrode layer improves the accessibility and diffusion of lithium ions in and out of the nanostructured silicon thin film layer during charging cycles, i.e., during lithiation and delithiation.
[0048] The present invention is further directed to a method for preparing a silicon composite material for use as a rechargeable battery anode, comprising the steps of: (i) providing an electrically conductive substrate comprising a copper or titanium foil; (ii) providing an adhesive layer attached to the foil comprising at least one or more metals and / or metal compounds; and (iii) forming an electrode layer comprising silicon attached to the adhesive layer by low pressure plasma enhanced chemical vapor deposition (PECVD). The method comprises forming a nanostructured silicon thin film layer as an anode layer on the copper or titanium foil comprising an adhesive layer comprising one or more metals and / or metal compounds, the forming process being configured to produce a nanostructured silicon thin film layer comprising a plurality of adjacent silicon columns and nanoparticle aggregates. As explained above, the nanostructured silicon thin film layer can provide significantly higher energy storage capacity, for example 10 times higher than prior art graphite anodes.
[0049] During the formation process, the silicon-based columns extend perpendicular to a surface of the foil including the adhesion layer. The silicon columns are disposed adjacent to one another while being separated by vertically extending interfaces, the interface separation being substantially parallel to the surface of the nanostructured thin film layer. Once formed, the silicon columns comprise amorphous silicon (am-Si) as verified by structural analysis of the thin film material.
[0050] As mentioned above, the term amorphous silicon should be interpreted to include original crystalline silicon, and thus amorphous silicon includes regions of nanocrystalline silicon up to about 30% of the nanostructured silicon thin film layer. Furthermore, the term "silicon" should also be interpreted to include silicon-based materials, i.e., silicon alloys, doped silicon.
[0051] The advantage of the method is that the silicon columns are formed in a self-assembled manner and randomly distributed across the foil, so there is no need to actively manipulate or control the column formation. Thus, the method of the present invention is a self-assembled, spontaneous process for forming nanostructured silicon thin film layers that does not include post-processing steps. As a result, the method is easily adapted to manufacture silicon-based anodes at industrial levels for commercialization.
[0052] In an embodiment, the formation process includes deposition of the anode layer by PPECVD, thereby allowing the deposition of a nanostructured thin film anode layer having a thickness of 1 μm to 30 μm.
[0053] The present invention is therefore directed to a method for preparing an anode device comprising a copper or titanium foil covered with a layer of silicon by depositing the silicon on the foil coated with one or more metals and / or metal compounds by low pressure PECVD. The PECVD process preferably comprises the use of a microwave plasma or a mixture comprising a silicon-containing gas and hydrogen, the formation process being configured to produce a nanostructured thin film layer.
[0054] In a further embodiment, the microwave plasma is generated by an elongated antenna wire, each end of the wire being coupled to a microwave generator.More preferably, the mixture of silicon-containing gas and hydrogen further comprises an alloying compound for forming a silicon alloy.
[0055] In a further embodiment, the PECVD process includes the use of a microwave plasma of a mixture of a silicon compound gas and hydrogen, H2. The silicon compound may be, for example, silane, SiH4, or a chlorosilane, such as SiCl4. Preferably, the silicon-containing gas is selected from the group including monosilane, disilane, trisilane, and chlorosilane.
[0056] The use of microwave frequencies reduces ion bombardment of the anode growth zone of the substrate during the formation process, resulting in increased growth rate of the anode layer.
[0057] In yet another embodiment, the mixture of silicon compound gas and H2 further comprises argon (Ar). Using such a mixture allows plasma to be maintained at low pressure and can promote the self-organized growth of nanostructured silicon thin film layer, i.e., silicon columns and column boundaries, i.e., interfaces therebetween. Here, self-organized growth means that the formation of silicon columns and nanoparticle aggregates and interfaces therebetween occurs spontaneously. The silicon columns are deposited in a substantially random manner across and along the foil, thus forming a substantially random arrangement. The self-organized formation of silicon columns can be seen as a one-step fabrication process, which avoids post-treatment of the foil or the deposited silicon anode layer.
[0058] Furthermore, the formation of the nanostructured thin film layer may include the addition of doping precursors to obtain either n-type or p-type doped nanostructured silicon thin film layers depending on the type of precursor, in an embodiment, the precursors are gaseous species that are added to a mixture of silane and hydrogen.
[0059] The PECVD process used is preferably a low pressure PECVD process. For example, in an embodiment, when a silicon compound gas, such as a mixture of silane and hydrogen, is used, the low pressure PECVD process includes a pressure of more than 0.15 mbar so that a tenable plasma can be maintained. In another embodiment, for example, when the mixture of silane and hydrogen further includes argon, the low pressure PECVD process includes a pressure of less than 0.15 mbar.
[0060] In a further embodiment, the PECVD process is a microwave PECVD process. To allow for large area production of the silicon anode layer, in an advantageous embodiment, the microwave plasma is generated by an elongated antenna wire, each end of which is coupled to a microwave generator. The elongated antenna wire provides a substantially linear and homogeneous field of microwave radiation in the plasma reactor during the formation process, so that a more homogeneous deposition of multiple silicon columns is achieved over a large area. In an embodiment, the length of the antenna wire is at least 50 cm, more preferably at least 100, such as 120 cm, preferably up to 200 cm, more preferably up to 150 cm. The length of the antenna wire directly affects the produced surface area of the nanostructured silicon thin film layer per unit time. Increasing the length of the antenna wire typically increases the achievable surface area of the nanostructured silicon thin film layer that can be produced per unit time.
[0061] Without any limitation of the inventive concept and without being bound by any theory on the deposition mechanism, it is believed that according to an embodiment, a method for the formation of nanostructured silicon thin films is configured to provide growth conditions for the silicon thin film, where the deposited silicon atoms experience relatively low surface mobility that results in the typical nanostructure of the silicon thin film.
[0062] The following non-limiting embodiments of the present invention are further described hereinafter with reference to the accompanying drawings, in which like letters and numbers refer to like parts and in which the figures are approximately drawn to scale. [Brief description of the drawings]
[0063] [Figure 1] 1 is an image showing an example of a rough copper foil surface (SEM). [Diagram 2] 1 is an image showing an example of a smooth copper foil surface (SEM). [Figure 3A] FIG. 1 is a diagram showing an example of a double-sided anode structure; [Figure 3B] FIG. 1 shows an example of a one-sided anode structure. [Figure 4] FIG. 1 shows the structure of a battery cell with a double-sided silicon anode, two single-sided cathodes, and two separators. [Diagram 5] 1 is a graph showing the grain size distribution of micropores in silicon. [Figure 6] 1 is a graph showing Raman spectroscopy of silicon. [Figure 7A] 1 is a graph showing the stability of silicon electrodes made on copper foils with ZnO coatings. [Figure 7B] 1 is a graph showing the stability of silicon electrodes fabricated on copper foils containing a chromate coating. [Figure 8] 1 is a cross-sectional SEM image of a silicon electrode. [Figure 9] 1 is a TEM image of a silicon electrode showing the grain structure. [Figure 10] 1 is an image showing a copper foil containing Si after undergoing several charge / discharge cycles in a coin cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0064] Figures 1 and 2 show the same copper foil, but different sides of the foil. Figure 1 shows a scanning electron microscope (SEM) image of the surface of the textured side of the copper foil, which can serve as a substrate for a silicon anode. The surface can have features with dimensions up to several micrometers. The textured copper foil has a roughness of approximately 1 micrometer. The deposited silicon layer follows the roughness of the surface.
[0065] In Figure 2, an SEM image of the opposite side of the copper foil is shown, which can also serve as a substrate for a silicon anode. Here, compared to the foil shown in Figure 1, the surface is smoother.
[0066] In Fig. 3, two schematic configurations of anode materials are shown. In Fig. 3A, a double-sided anode is shown, where according to an embodiment of the present invention, the top layer is an electrode layer (1) made of silicon, the middle layer is an adhesion layer (2) made of, for example, ZnO, and the middle layer is a current collector (3) made of copper or titanium. The current collector (3) is on the other side covered by the adhesion layer (2) and the electrode layer (1). In Fig. 3B, a single-sided anode structure is shown, which includes an electrode layer (1) made of silicon, the middle layer is an adhesion layer (2) made of, for example, ZnO, and the middle layer is a current collector (3).
[0067] In Figure 4, the structure of a battery cell is depicted diagrammatically, with a double-sided silicon anode (6), two single-sided cathodes (4), and two separators (5). This represents a typical layout for an electrode stack inside a lithium-ion battery cell.
[0068] Figure 5 shows a typical pore size distribution of porous silicon deposited using the PECVD process measured using the Barrett-Joyner-Halena method. It shows that the average pore size is less than 100 nm, with most of the pore volume being made up of pores with sizes between 10 and 30 nm. Integrating the pore sizes shows that the porosity of the material is about 20%.
[0069] In FIG. 6, Raman spectroscopy of silicon is shown. -1 The broad peak at 520 cm is indicative of the presence of amorphous silicon. -1 The lack of a sharp peak at 0.05 indicates that the silicon is primarily amorphous.
[0070] Figure 8 is a cross-sectional SEM image illustrating a typical material structure, depicting a combination of column-like structures and particle aggregates. It also clearly depicts that the silicon layer follows the structure of the substrate, implying that the silicon loading is homogeneously distributed.
[0071] Figure 9 shows a TEM image of the particle aggregate structure that makes up the silicon anode layer. It shows that the primary silicon particles that make up the anode layer are in the size range of 10-20 nm, and that there is sufficient space between the particles to allow both expansion of the silicon upon lithiation and transport of electrolyte through the layer.
[0072] Figure 10 shows a comparison between three anodes repeated in a coin cell. Foil 1 is a copper foil with a thin layer of ZnO and a coating of amorphous Si. Foil 2 is a copper foil with a thin layer of Cr2O3 and a coating of amorphous Si. Foil 3 is a copper foil with a thin layer of Cr2O3 deposited on top of a thin layer of ZnO and a coating of amorphous Si.
[0073] The following non-limiting examples are provided to illustrate the present invention. EXAMPLES
[0074] Copper foils that provide good adhesion were also prepared using an electrodeposition process involving electrochemical deposition of a thin ZnO layer (foil 1 in FIG. 10). Next to it, a copper foil with a Cr2O3 coating deposited thereon was also prepared using electrodeposition (foil 2 in FIG. 10) and a copper foil with an Al-doped ZnO coating deposited by sputtering on a thin Cr2O3 layer deposited using electrodeposition (foil 3 in FIG. 10). The elemental composition of the copper foil surface was measured using X-ray photoelectron spectroscopy. The measurement results shown in Table 1 indicate that the surface of the copper foil is covered with a layer of metal oxide, which is ZnO, Cr2O3 or Al-doped ZnO.
[0075] [Table 1]
[0076] In foil 1, a smaller percentage of Cu is measured in addition to a larger percentage of Zn, from which it can be concluded that the thickness of the layer of ZnO is less than 5 nm or that the surface is only approximately 90% completely covered with ZnO. The presence of O indicates that Zn is oxidized to ZnO. In foil 2, Cu is coated with a Cr2O3 coating based on the Cr / Cu ratio or the partial coverage of the Cu foil surface, also with a thickness of less than 5 nm. Foil 3 has a dense coating of Al-doped ZnO of 5 nm based on the average sputter deposition rate of the sputtering tool. The layer of Al-doped ZnO is almost certainly very dense since the signals of Cu and Cr are extremely small compared to that of Zn. The concentration of Al-doping is approximately 10%. In all samples, the presence of carbon was most likely caused by sample contamination due to exposure to air, while the presence of P, Cl and S is most likely a result of residuals from foil manufacturing.
[0077] To test the adhesive strength of silicon to copper foil, coin cells were assembled and electrodes consisting of Cu foil, adhesive layer, and Si and Li counter electrodes were tested for several cycles. Post-mortem images after several cycles are shown in Figure 10. For the foil with a ZnO layer between Cu and Si, the Si was still attached to the Cu foil, but the Si had almost completely detached from the Cr2O3 coated foil. EXAMPLES
[0078] The cycling stability of electrodes made with copper foil containing a zinc oxide adhesive layer is compared with copper foil containing a coating made of chromate and foil without an adhesive layer. All foils are 8-10 microns thick. Lithium metal was used as the counter electrode and in this example the silicon-containing copper foil worked as the cathode rather than as the anode. These experiments were used for comparison and stability testing so that the results can be extrapolated to electrode layers containing silicon as the anode.
[0079] Electrodes prepared without an adhesive layer were not mechanically stable and could not be used to prepare coin cells, so no electrochemical measurements were possible.
[0080] The electrodes made of copper foil with chromate and zinc oxide coatings were placed in coin cells. The electrolyte used contained LiPF6 with a concentration of 1M in a 1:1 mixture by volume of ethylene carbonate and diethyl carbonate. To this electrolyte, 2% by weight of vinylene carbonate and 25% by weight of fluoroethylene carbonate were added.
[0081] The cell was cycled at a constant capacity of 1800 mAh per gram of silicon, and the cycling results are given in Figure 7. The results show that the stability of the electrode is greatly improved by using ZnO coated copper foil compared to foils with a chromate coating.
Claims
1. 1. A silicon composite material for use as a rechargeable battery anode, comprising: (i) an electrically conductive substrate comprising a copper or titanium foil; (ii) an adhesive layer attached to the foil comprising at least one or more metals and / or metal compounds; and (iii) an electrode layer comprising silicon attached directly to the adhesive layer, wherein the metals and / or metal compounds comprise zinc and / or tin, and oxides of zinc and / or tin, respectively, and the adhesive layer has a thickness comprised between 0.1 and 5 nm; A silicon composite material, wherein the silicon of the electrode layer comprises a plurality of adjacent columns and nanoparticle aggregates, the columns extending vertically from the foil surface, adjacent columns being separated by vertically extending column boundaries.
2. 2. The silicon composite material of claim 1, wherein the oxide of zinc is doped with aluminum and the oxide of tin is doped with fluorine or indium.
3. 3. The silicon composite material according to claim 1 or 2, wherein the compound is ZnO.
4. 4. The silicon composite material according to claim 1 , wherein a silicon layer and an adhesive layer are present on both sides of the foil.
5. 5. The silicon composite material according to claim 1 , wherein the adhesion layer has a thickness in the range of from 1 to 2 nm.
6. The silicon composite material of claim 1 , wherein the silicon has an amorphous structure containing nanocrystalline regions.
7. 10. The silicon composite material of claim 1, wherein the columns contain up to 30% nanocrystalline silicon.
8. The silicon composite material according to any one of claims 1 to 7, wherein the electrode layer further comprises a silicon alloy which is Si-C and / or Si-N.
9. 9. The silicon composite material according to claim 1 , wherein the electrode layer comprising silicon has a porosity of from 10% to 50%.
10. The electrode layer has a thickness of 1 μm to 30 μm, or a thickness of 0.1 to 4.0 mg / cm 2 10. The silicon composite material of claim 1 having a mass loading of up to 1000 .mu.m.
11. 11. A rechargeable battery comprising an electrolyte, a cathode layer, a separator layer and the silicon composite material of any one of claims 1 to 10, wherein the electrolyte is disposed between the cathode layer and the silicon composite material and further comprises a lithium salt compound.
12. 12. The rechargeable battery of claim 11, wherein the cathode layer comprises nickel manganese cobalt oxide, lithium cobalt oxide, lithium cobalt aluminum oxide, lithium manganese oxide, or lithium iron phosphate.
13. 1. A method of preparing a silicon composite material for use as a rechargeable battery anode, comprising: (i) providing an electrically conductive substrate comprising a copper or titanium foil; (ii) providing an adhesion layer attached to the foil, the adhesion layer having a thickness in the range of 0.1 to 5 nm, the adhesion layer comprising at least one or more metals comprising zinc and / or tin, and / or metal compounds comprising oxides of zinc and / or tin; and (iii) forming an electrode layer comprising silicon attached directly to the adhesion layer by low pressure PECVD; A method wherein the silicon of the electrode layer comprises a plurality of adjacent columns and nanoparticle aggregates, the columns extending vertically from the foil surface, adjacent columns being separated by vertically extending column boundaries.
14. 14. The method of claim 13, wherein the PECVD process comprises the use of a microwave plasma or a mixture comprising a silicon-containing gas and hydrogen, and the layer formation process is configured to produce a nanostructured thin film layer.
15. 15. The method of claim 14, wherein the microwave plasma is generated by an elongated antenna wire, each end of the antenna wire being coupled to a microwave generator.
16. 16. The method of claim 14 or 15, wherein the mixture of silicon-containing gas and hydrogen further comprises an alloying compound for the formation of a silicon alloy.
17. 17. The method of any one of claims 14 to 16, wherein the mixture of silicon-containing gas and hydrogen further comprises argon.
18. 18. The method of any one of claims 15 to 17, wherein the silicon-containing gas is selected from the group comprising monosilane, disilane, trisilane and chlorosilane.
Citation Information
Patent Citations
Negative electrode for non-aqueous electrolyte secondary battery, its manufacturing method, and non-aqueous electrolyte secondary battery
JP2006164793A
Electrode for bipolar battery
JP2007329004A
Negative electrode for secondary battery, copper foil for electrode, secondary battery, and process for producing the negative electrode for secondary battery
JP2010282959A
Surface treatment copper foil for negative electrode, negative electrode and lithium ion secondary battery using the same
JP2015198020A
Rechargeable battery and manufacturing method thereof
JP2018517232A